Cryptocurrency Blockchain Technology in the Digital Revolution Era - Astuti, Intan Dwi; Rajab, Suryazi; Setiyouji, Desky (Pandawan, 2022)
Cryptocurrency is a blockchain-based technology that is often used as a digital currency. Digital money is different from conventional money, this type of money does not have a physical form but only a block of data bound by a hash as validation. The data is spread to every cryptocurrency user who is in the environment. So that when a user makes a transaction, data mining will be carried out. Cryptocurrencies have several advantages but also have disadvantages when used as currency, from a legal point of view there is still no law governing the circulation of currency in digital form (cryptocurrency). The government must recognize digital currency so that it can be accepted by the general public as a means of payment. For now, the government has not recognized digital money (cryptocurrency) as a currency, because Cryptocurrency is a new phenomenon by some people in Indonesia. The rapid development of technology in the 4.0 revolution era, in the next few years money in physical form will be replaced by digital money, seeing the many conveniences provided by using digital money.